Optimising Educational Practices in Simulation‐Based Nursing Education: Results of A National Survey - Mohammad Alsadi (18024379) (2025)
Introduction Simulation‐based education is recommended in nursing education. In the same stream, different educational practices are utilised using different simulation designs to optimise the learning outcomes. The current study aims to evaluate the better simulation designs in undergraduate nursing education and the associated “better fit” educational practices. Methods Descriptive, correlational design using a self‐reported online questionnaire. Results A total of 966 undergraduate nursing students at 16 universities in Jordan participated in the survey. Nursing students perceive “support” during the simulation‐based educational activity, clear “objective and information,” and high “fidelity” as the important dimensions of simulation designs. An “active learning” experience was considered the most important educational practice. Conclusions The simulation laboratories need to support students, clarify the objectives, and provide needed information. High levels of fidelity are also needed, coupled with interventions to support students' active learning experiences. Patient or Public Contribution No Patient or Public Contribution. Other Information Published in: Nursing Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/nop2.70172